Medical therapeutics (W. B. Saunders, 1998)
The book is designed to guide both seasoned and apprentice clinicians as they apply available therapies to a broad range of medical disorders. The material is presented in outline format to enable you to identify quickly specific recommendations for treatments. Descriptions of disease manifestations and pathophysiology are relatively brief.